2023
DOI: 10.1002/jmri.28630
|View full text |Cite
|
Sign up to set email alerts
|

Improving Noninvasive Classification of Molecular Subtypes of Adult Gliomas With Diffusion‐Weighted MR Imaging: An Externally Validated Machine Learning Algorithm

Abstract: BackgroundGenetic testing for molecular markers of gliomas sometimes is unavailable because of time‐consuming and expensive, even limited tumor specimens or nonsurgery cases.PurposeTo train a three‐class radiomic model classifying three molecular subtypes including isocitrate dehydrogenase (IDH) mutations and 1p/19q‐noncodeleted (IDHmut‐noncodel), IDH wild‐type (IDHwt), IDH‐mutant and 1p/19q‐codeleted (IDHmut‐codel) of adult gliomas and investigate whether radiomic features from diffusion‐weighted imaging (DWI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…However, when examining the external UCSF dataset, the addition of N4/z-score normalized radiomics for ADC outperformed the other approaches for both the IDH-wt and IDH-mut non-codel groups. These results are in part consistent with the recently published work of Guo et al, 11 which showed a significant performance increase for prediction of IDH-wt and IDH-mut non-codel group in both the internal and external dataset by adding normalization-naïve ADC radiomics using a random forest multiclass model. The fact that in the external validation, in contrast to Guo et al, we only saw a performance increase with normalized, but not naïve ADC radiomics, highlights the importance of intensity normalization of ADC for improving the generalizability of radiomic-based prediction models.…”
Section: Discussionsupporting
confidence: 92%
“…However, when examining the external UCSF dataset, the addition of N4/z-score normalized radiomics for ADC outperformed the other approaches for both the IDH-wt and IDH-mut non-codel groups. These results are in part consistent with the recently published work of Guo et al, 11 which showed a significant performance increase for prediction of IDH-wt and IDH-mut non-codel group in both the internal and external dataset by adding normalization-naïve ADC radiomics using a random forest multiclass model. The fact that in the external validation, in contrast to Guo et al, we only saw a performance increase with normalized, but not naïve ADC radiomics, highlights the importance of intensity normalization of ADC for improving the generalizability of radiomic-based prediction models.…”
Section: Discussionsupporting
confidence: 92%
“…There are growing number of studies using machine learning algorithms to predict molecular subtypes such as 1p/19q co-deletion and IDH mutations [ 7 , 21 , 30 33 ]. However, most of these studies only used conventional anatomical MR sequences because of the widespread usage.…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation is the exclusion of functional MRI techniques such as diffusion-and perfusion-weighted imaging from our analysis. These techniques can provide valuable insights into tumor cellularity and vascularity, complementing conventional imaging modalities [38,46,47]. However, their application is not widespread in clinical practice, being more commonly employed for research purposes.…”
Section: Discussionmentioning
confidence: 99%